Peningkatan Tahsin Al-Qur’an melalui Gerakan Pecinta Al-Qur’an di Taman Pendidikan Al-Qur’an Desa Carang Wulung Kecamatan Wonosalam Kabupaten Jombang - Nur 'Azah; Abdullah Aminuddin Aziz; Muhammad Al-Fatih; Masrokhin; Lik Anah (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
This study aims to determine the improvement of tahsin Al-Qur'an through the Al-Qur'an lovers movement as well as its inhibiting and supporting factors. The research used used qualitative research with a case study approach. The research subjects amounted to 15 children. Data collection techniques used interviews, observation and documentation. Data analysis using triangulation. The conclusion of the study was that the improvement of tahsin al-Quran through the movement of Al-Qur'an lovers at the Al-Qur'an Education Park in Carang Wulung Village, Wonosalam District, Jombang Regency went well during the activity.. Then the use of learning methods applied by the Al-Qur’an lovers movement in improving children's tahsin Al-Qur’an is the method of lecture, question and answer, demonstration and discussion. The inhibiting factors of this activity are that there are children who are not present in teaching and learning activities and there are some children who tend to play and joke with their friends during tahsin activities. The supporting factors for this activity are the use of learning methods used in delivering quality, good and supportive tahsin material, children are enthusiastic in tahsin activities through the movement of Al-Qur’an lovers because during the activity they always play an active role in learning to read the Qur'an and the ability to manage tahsin activities well by the teacher in conditioning this activity. Recommendations for further research can examine or study related to tahsin Al-Qur'an at different age levels, different teaching methods and others.